High-Density EEG Source Localisation of averaged interictal epileptic Discharges validated by surgical Outcome - Bernd J. Vorderwülbecke; Margherita Carboni; Sebastien Tourbier; Laurent Spinelli; Denis Brunet; Martin Seeber; Christian M. Korff; Shahan Momjian; Maria Vargas; Margitta Seeck; Serge Vulliemoz; Jonathan Wirsich (Scientific Data)
Abstract Electroencephalographic source localisation (ESL) of interictal epileptiform discharges is a valuable tool for presurgical evaluation of pharmacoresistant focal epilepsy. Various forward models, inverse solutions algorithms, and software packages have been published. However, clinical validation studies are based on heterogenous end points and study cohorts. To allow comparison of different interictal ESL methods within one standardised dataset, we provide deidentified clinical data of 44 well-characterised patients with pharmacoresistant focal epilepsy and a first resective surgery, validated by 12-month postsurgical outcome. Thirty patients had favourable outcomes, including 28 with complete seizure freedom, indicating that the epileptogenic zone was correctly estimated. For each patient, pre-processed individual structural MRI, 257-channel EEG averages of homologous discharges, postsurgical structural neuroimaging, and detailed clinical and technical information are given. In patients with favourable outcomes, source maxima of averaged discharges were <10 mm remote from the resection in 67% and within a sublobe affected by the surgery in 83%. Future validation studies of new ESL approaches can be compared to this benchmark.